The Use of Messaging Applications among University Students: A Case at Universiti Kebangsaan Malaysia - Hassan, Rosilah; Khalil Abd, Sura; Wahi, Wahiza; Hazwani Siran, Fatin (International Journal of Engineering and Technology, 2018)
Since the introduction of smart phones in 1995 by IBM, more and more applications for communication have been created as the medium to transmit messages and fulfill various needs of Android/iOS users.Â Most of messaging applications are free of charge and user-friendly as they support the functions of sending or receiving various types of file. This paper reports on a case study on the use of the most trending and active user messaging apps worldwide, e.g. WhatsApp, Facebook Messenger, and WeChat. WhatsApp, among university students at Universiti Kebangsaan Malaysia (UKM). Data for this study were gathered through the questionnaire distributed to sixty respondents. Findings of this study reveal that majority of the respondents use WhatsApp the most to send and receive messages. Most of them agree that they utilize messaging apps for chatting and discussing group assignments. A large portion of the students agrees that they use slang or abbreviation in messaging apps. 50% of the respondents agree that they received false news or fraud message in messaging apps. Most of the respondents agree that they carry out some research on Google to recognize false news. Most of the respondents agree that they feel negative emotion when waiting for a reply in a very long time. Real time chatting and sending message at no cost are the main reasons for choosing messaging apps. Receiving false news and redundant messages are the major drawbacks of messaging apps perceived by the respondents. In general, most of the respondents agree that the technology of messaging apps bring more advantages than disadvantages to general users.Â Â